The Peregrine Ion Trap Mass Spectrometer (PITMS): Results from a CLPS-delivered Mass Spectrometer - Barbara A. Cohen; Simeon J. Barber; Aleksandra J. Gawronska; Feargus A. J. Abernethy; Natalie M. Curran; Phillip A. Driggers; William M. Farrell; David J. Heather; Christopher Howe; Peter F. Landsberg; Veneranda López-Días; Andrew D. Morse; et al. (The Planetary Science Journal)
The Peregrine Ion Trap Mass Spectrometer (PITMS) was a mass spectrometer designed to measure lunar gases. PITMS flew on the first flight of Astrobotic’s Peregrine lander via the Commercial Lunar Payload Services (CLPS) program in 2024 January. After launch, the lander suffered a propulsion system anomaly that prevented the mission from reaching the Moon, but PITMS collected 80 high-quality spectra while in cislunar space. PITMS observed abundant outgassing products from the Peregrine lander, including water, MON-25 oxidizer from the propulsion system leak, and traces of combustion products. PITMS data help constrain the nature of the propulsion system failure: oxidizer molecular ratios show that the leak released molecules rapidly enough for them to fully dissociate, and the high observed abundances imply that the oxidizer traveled within the lander surfaces rather than jetting into space. The amount of water offgassed by the spacecraft is substantially more than other planetary spacecraft, so the PITMS results suggest that instruments flying in the CLPS paradigm need to consider lander cleanliness. Though not successful in measuring the native lunar exosphere, the PITMS results showcase the capabilities of a mass spectrometer on board a lunar lander, along with lessons in pragmatism and flexibility that would enable such an instrument to ultimately be successful in the CLPS initiative.